Green Fiscal Policy and Urban Land Green Utilization Efficiency - Yifei Wang; Sijia Li (Land)
China is at a critical stage in addressing environmental issues and achieving sustainable development. To effectively promote environmental protection and the construction of an ecological civilization, government policy support has become essential. Accurately assessing the impact of green fiscal policy (GFP) on urban land green utilization efficiency (LGUE) is significant for achieving a “win–win” situation between economic development and environmental protection and for implementing a green and low-carbon path. This study evaluates the LGUE improvement effect of GFP using the DID method with the panel data of 270 cities in China from 2008 to 2019. We find that the GFP significantly improves the urban LGUE level. The mechanism analysis shows that the GFP improves LGUE through green technological innovation, industrial structure upgrading, and environmental regulation intensity. The heterogeneity analysis shows that the LGUE improvement effect of GFP is stronger for eastern cities and non-resource-based cities. This study has important theoretical and practical significance for coordinating green fiscal policies and deepening the promotion of the sustainable use of land resources.